2008
DOI: 10.1089/ees.2006.0132
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Domestic Wastewater by Electrocoagulation in a Cell with Fe–Fe Electrodes

Abstract: In this study, the potential to treat domestic wastewater (DWW) using an electrocoagulation (EC) process was tested on two different samples, one of which was heavily loaded [380 mg chemical oxygen demand (COD)/L]; the other was weakly loaded [260 mg COD/L]. The samples were supplied from the Istanbul-Yenikapi DWW pretreatment plant. The experimental studies were conducted within an electrolysis cell with Fe-Fe electrodes. In this cell, under optimum operational conditions in the form of electrical power and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…From the literature, the most common approach involves plate electrodes (aluminum or iron) and continuous operation (El-Naas et al, 2009). From previous literature (Mouedhen et al, 2008;Zaroual et al, 2009;Lacasa et al, 2011;Kurt et al, 2008), it was found that the perforated anode sheet with larger surface area achieved the maximum percentage removal than the nonperforated anode; this is the same as results obtained from this study. The shape of the electrodes affects the pollutant removal efficiency in the electrocoagulation process.…”
Section: Comparison Between the Anode Geometry Of Three Types Of Cellssupporting
confidence: 87%
See 1 more Smart Citation
“…From the literature, the most common approach involves plate electrodes (aluminum or iron) and continuous operation (El-Naas et al, 2009). From previous literature (Mouedhen et al, 2008;Zaroual et al, 2009;Lacasa et al, 2011;Kurt et al, 2008), it was found that the perforated anode sheet with larger surface area achieved the maximum percentage removal than the nonperforated anode; this is the same as results obtained from this study. The shape of the electrodes affects the pollutant removal efficiency in the electrocoagulation process.…”
Section: Comparison Between the Anode Geometry Of Three Types Of Cellssupporting
confidence: 87%
“…This trend was observed for the three cells due to the fact that as the current density increased, the formation of flocs of aluminum hydroxide at the anode of the cell increased and this enhanced the rate of adsorption of β-naphthols on the flocs of aluminum hydroxide. Also, by increasing the current density of the cell, the amount of hydrogen bubbles at the cathode increased, resulting in a greater upward flux and a faster removal of β-naphthols and sludge flotation (Kurt et al, 2008;. At high current density, the quantity of Al 3+ from anode dissolution increases according to Faraday's low.…”
Section: Effect Of Current Densitymentioning
confidence: 99%
“…Copper ion, beyond hydroxide precipitation and absorption on the Al(OH) 3 4 -flocs, is also partially removed by direct electroreduction at the cathode or by electroless deposition according to the reaction as follows as [11,17] …”
Section: Analysis Of Mechanismmentioning
confidence: 99%
“…The fluidized bed method was used to provide oxygen for the treatment system and prevent the clumping of Fe/C, therefore, reduce the passivation problem of the particles of Fe/C. The mechanism of EC/FB/ME process is summarized as follows as [2][3][4]:…”
Section: Introductionmentioning
confidence: 99%
“…With the strict environmental regulations regarding wastewater discharge in recent years, electrochemical technology has been widely utilized in the treatment of various types of wastewaters such as textile [4][5][6], oil and oil-in-water emulsion [7][8][9], laundry [10][11][12], livestock [13][14][15], leachate [16][17][18], and sewage [2,[19][20]. The use of electrochemical technology provides several benefits, such as strong oxidation, easy operation, no limitation by a seasonal variation, variable capability to influent flux and quality, and rapid treatment time, over the conventional wastewater treatment methods.…”
Section: Introductionmentioning
confidence: 99%